HUBUNGAN PENGGUNAAN KONTRASEPSI SUNTIK DEPO MEDROXY PROGESTERONE ACETATE (DMPA) DENGAN PENINGKATAN BERAT BADAN DAN GANGGUAN HAID DI PUSKESMAS RIJALI KOTA AMBON - Asriaty Dinopawe; Melawati Wakano; Priska Yulia Louhenapessy (STIKES Pasapua Ambon, 2022)
Introduction: Contraception is a way or method that aims to prevent conception so that pregnancy does not occur. Judging from the initial data, there were problems at the Riajli Health Center, namely the number of mothers who used depo medroxy progesterone acetate (DMPA) injection contraceptives with increased body weight and menstrual disorders. The general objective of this study was to determine the relationship between mother’s knowledge about the use of contraceptives depo medroxy progesterone acetate (DMPA) injection contraception with increased body weight and menstrual disorders at the Rijali Health Center, Ambon City. Method: The research method used in this study is descriptive analytic using a cross sectional approach. The population in this study were all mothers who used depo medroxy progesterone acetate (DMPA) injectable contraception. Total sampling technique with a total sample of 37 respondents. Collecting data by interview using a questionnaire. The results of this study indicate that respondents who have the At level show that the distribution of respondents based on the dependent variable weight gain as many as 25 respondents (67.5%) experienced weight gain and as many as 12 respondents (32.5%) did not gain weight. it can be seen that the distribution of respondents based on the dependent variable of menstrual disorders as many as 25 respondents (67.5%) experienced menstrual disorders and as many as 12 respondents (33.5%) did not experience menstrual disorders. Results: The results of the chi-square correlation test to see the relationship between the independent variable (use of depo medroxy progesterone acetate DMPA injection contraception) and the dependent variable (weight gain) found p = 0.002, with a p value <α = 0.005, then H0 was rejected and Ha was accepted directly . Conclusion: there is a relationship between the use of depo medroxy progesterone acetate (DMPA) injection contraception and weight gain.